Measuring corporate social performance - Thao, Le Ha Nhu; Anh, Doan Ngoc Phi; Velencei, Jólan (Serbian Journal of Management, 2018)
Business and researchers have paid increasingly more attention to corporate social responsibility (CSR) disclosure in term of their sustainable reports. These disclosures supply information for not only managers in strategic decision-making but also other stakeholders in measuring and evaluating corporate social performance (CSP). Although the development of literature on CSR disclosure, the CSR’s measurement is not yet unified because of different perspective and methodology. The question is how to measure CSP through analyzing CSR disclosure. This paper aims to present theoretical background of CSR and CSR disclosure. Based on the conceptual framework, the research exposes the drivers of CSR reporting as well as debates prior research on CSR disclosure and its consequences. Furthermore, a measurement method of CSP proposed built on CSR disclosure index in this paper. It devotes to enrich the corporate social responsibility reporting literature, offers implications for practice as well as outlines promising avenues for future research, especially in the differences of CSR disclosure among different countries.